Richard E. Caves y Harry G. Johnson (compiladores). Readings in international economics. Homewood, Ill. : Richard D. Irwin, Inc., 1968. xii, 604 p. - Bueno, Gerardo M. (El Colegio de México A.C., 1969)
RICHARD E. CAVES y HARRY G. JOHNSON (compiladores), Readings in International Economics. Homewood, III., Richard D. Irwin, Inc., 1968.